Analysis Of Product Quality, Brand Image, And Country of Origin On Interest To Buy Oppo Smartphone (Case Study On Employees Of Air Anyir Bangka PLTU) - Ahmad Alif Rahmadisa Putra (Jurnal Manajemen Dayasaing, 2022)
This type of study is a survey. The population in this study is the employee of PLTU Air Anyir Bangka who are using Oppo Smartphone product. The sampling method is saturated sample (census technique) with 92 respondents. Data analysis technique used is multiple linear regression. The results of this study indicate that: (1) product quality has no effect on buying interest with regression value of 1,564 with significant value 0,121; (2) brand image have positive effect on buying interest with regression value equal to 3,067 with significant value 0,003; (3) country of origin has no effect on buying interest with regression value of 0,227 with significant value 0,821; and (4) product quality, brand image, and country of origin have a positive effect on buying interest with a significance level of 0,000 meaning less than 0,05 (p0,05).